A business case for engaging the private sector in climate-smart solutions for smallholder farmers - Mutamba, Manyewu; Ajayi, Oluyede C. (Technical Centre for Agricultural and Rural Cooperation, 2018)
Large and growing numbers of poor rural households depend on climate-sensitive agriculture and operate on the margins of the mainstream economy. This combined with a broken public extension service and faltering international development efforts places millions of smallholder farmers at disproportionately high risk from a changing climate. Acknowledging the magnitude of the challenge and the required pace and scale of response, coupled with honest introspection on past performance, has prompted the need to look beyond the public sector for delivering climate-smart solutions. Harnessing the financial, technological and intellectual capital in the private sector to complement public sector-driven climate responses is a new dimension in delivery of sustainable climate-smart solutions at scale.